Rangeland ecosystem services: shifting focus from supply to reconciling supply and demand - Yahdjian, María Laura (2015)
Ecosystem services have been extensively studied in recent decades. Most of the thousands of scholarly papers published on the subject have focused on describing the production, spatial extent, and valuation of such services. Human reliance on ecosystem services is a function of ecosystems’ capacity to supply and societal demand for these benefits. However, considerably more attention has been devoted to the supply side than to the demand for them. Sustainable land management depends on reconciling supply of and demand for ecosystem services among different stakeholders. The emphasis is now shifting from the supply of ecosystem services to attaining a balance between supply and demand. Here, we illustrate the demand for rangeland ecosystem services, describe current changes in societal demand, and present a specific provisioning service to exemplify the dynamic nature of reconciling ecosystem-service supply and demand.